COMMUNITY PERCEPTIONS OF EARLY ADULT DOWN SYNDROME A SYSTEMATIC REVIEW - Nurzaki Alhafiz; wazirotus sakinah; Agus Mursidi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Background: society's perception of Down syndrome in early working adults . Objective: to determine the public's perception of Down syndrome in early adulthood. Method: the source of the article used was obtained from a search via Google Scholar. A literature search with the same theme contained 17,700 articles and filtering was carried out according to the theme, including 17 articles. Article searches are limited from 2019-2024. After the article is obtained, the article is reviewed until it reaches the stage of creating a systematic review. The keywords used in the article search are